PHOTO PHYSICAL PROPERTIES OF TWO COUMARIN DERIVATIVES USING SOLVATOCHROMIC SHIFT METHOD: Life Science-Spectroscopy - D. NAGARAJA; N.R. PATIL; .A.KUSANUR, RAVIRAJ; H.D. PATIL; R. M. MELAVANKI (International Journal of Life Science and Pharma Research, 2013)
The ground state (µg) and excited state (µe) dipole moments of two coumarin derivatives namely MDTC and BDTC were estimated in various solvents. The dipole moments were estimated from Lippert, Bakhshiev and Kawaski-Chamma-Viallet equations by using the variation of stokes shift with the solvent dielectric constant and refractive index. Ground state dipole moments were also calculated theoretically by DFT studies using Gaussian 03 software. It was observed that the excited state dipole moments calculated by solvatochromic shift method were greater than the ground state dipole moments indicating a substantial redistribution of the πelectron densities in a more polar excited state for both the coumarin derivatives.